The Stylistic Form and Meaning of Imperative and Prohibition Structures in al-Qira’ah al-Wafiyah Book l Shiyaghu wa Ma‘ani Asalibi al-‘Amr wa al-Nahy fi Kitabi al-Qira’ah al-Wafiyah - Zaid, Abdul Hafidz; Setiadi, Alif Cahya; Qonita, Sumayyah Alifatun (Universitas Islam Negeri Raden Intan Lampung, 2023)
Imperative and prohibition structures are the significance knowledge in Arabic learning about the forms and meanings. This study aimed to identify and analyze the stylistic form and meaning of imperative and prohibition structures in al-Qiroah al-Wafiyah Book by rethorical aspects. The qualitative desk research was applied with mainly the descriptive method in processing and presenting various styles of imperative and prohibition within the al-Qiroah al-Wafiyah book as the primary source. Those structures were collected by documentation technique and analyzed by using the content analysis and classifying the styles based on the rethoric analysis including both form and meaning. The result of the analysis showed that the occurrence of 44 styles of both structures, 35 styles of imperative and 9 styles of prohibition in detail. Moreover, the imperative forms consist of imperative verb, imperative noun, imperative infinitive, and imperative present tense. In addition, the prohibition froms encompassed only the present tense with the final “no”. In line to the meaning of the imperative constructions, it pointed several reliances; guidance, permission, honor, consideration, formation, and supplication. The prohibiton pointed the sense of guidance and hatred. By this research, it is possible to differentiate its structure and more realize that each structure has its style and meaning.